Perancangan Multimedia Interaktif Untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Dasar Desain Grafis Menggunakan Model Pembelajaran Picture and Picture di SMK Negeri 4 Gorontalo - Sumantri Iyohu; Muhammad Rifai Katili; Agus Lahinta (Inverted: Journal of Information Technology Education, 2021)
The basic subjects of graphic design at SMK Negeri 4 Gorontalo are subjects that are in great demand by students. Therefore, in order to improve the learning outcomes of learners, it is necessary to make some innovations in learning. However, in reality most teachers are not used to using interactive learning media and the cost of interactive learning media that attracts quite expensive prices is one of the inhibiting factors in learning. Therefore, it is considered necessary to develop an innovative and interesting learning media to be able to help students in understanding the material learned amid the difficulty of teachers obtaining interactive learning media that supports the learning process. The research conducted aims to 1). Describes the steps to design interactive multimedia-based picture and picture model learning media, and 2). Knowing the feasibility of learning media multimedia-based interactive picture and picture models according to material experts, media experts and users (students). The method used in the research was reseach and development method with ADDIE model with the results of learning media feasibility test by material expert showed feasibility percentage of 97.5% with "very feasible" category, media feasibility result according to media expert showed feasibility percentage of 79.2%% with "very feasible" category, as well as service result in user response (student) of 94.5% and categorized as "very feasible". So that it can be concluded that Interactive Learning Media based on Multimedia by using Picture and Picture learning model is very feasible to be used in the learning process. Keywords: Interactive; Multimedia; Picture and Picture.